Transparansi Informasi Dalam Pembangunan di Desa Pusungi Kecamatan Ampana Tete Kabupaten Tojo Una-una - Sintiya Didipu; Ellys Rachman; Andi Yusuf Katili (Public Inspiration : Jurnal Administrasi Publik, 2025)
This study aims to determine the level of information transparency in development in Pusungi Village, Ampana Tete District, Tojo Una-una Regency. The focus of this study is information access, community participation in development, and officials' understanding of information management. The research method used a descriptive qualitative approach. Data collection techniques were conducted through in-depth interviews with several informants, observation, and recording of secondary data related to the research problem. The study concluded that Pusungi Village still lacks access to information from the village government to the community regarding upcoming development projects due to several important interrelated factors. Community participation in village development does not emerge spontaneously but needs to be actively fostered by the village government. Village governments can foster community participation through several strategic steps: holding regular deliberations, providing clear and transparent information, involving various community groups, and improving village officials' understanding of information access and management will have a direct impact on increasing community participation, strengthening citizen trust in the village government, and ensuring that every policy or program is implemented transparently and effectively.